THE INFLUENCE OF DIVIDEND POLICIES, DEBT POLICIES, PROFITABILITY, ASSET STRUCTURE, AND COMPANY SIZE ON THE VALUE OF MANUFACTURING COMPANIES IN BEI 2013-2019 - Mujino, Mujino; Wijaya, Adi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to examine and analyze the effect of dividend policy, debt policy, profitability, asset structure, and company size on the value of manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2013-2019. The company characteristics indicators used include dividend policy, debt policy, profitability, asset structure, and company size against firm value. Dividend Policy is based on the Dividend Payout Ratio (DPR), Debt Policy is based on (DER), Profitability is proxied by Return On Assets (ROA), Asset Structure is based on Fixed Assets and Total Assets, Company Size is based on LN Total Assets and Company Value prioritized by Price to Book Value (PBV). This study uses secondary data from financial reports and annual reports of companies included in manufacturing companies during 2013 to 2019. The research sample was determined using a purposive sampling method, so that the sample obtained was around 9 companies. The results of hypothesis testing are only Debt Policy, Profitability, Asset Structure, and Company Size that affect Firm Value. Meanwhile, the Dividend Policy has no effect on Company Value.